Design and Planning of Mine Drainage Systems at PT. Pertama Mina Sutra Perkasa, Puger District, Jember Regency, East Java, Indonesia - Malik, Aldy Maulana; Sari, Avellyn Shinthya; Putri, Fairus Atika Redanto (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
PT. Pertama Mina Sutra Perkasa, a limestone mining company, operates in Grenden Village, Puger District, Jember Regency, East Java Province. Utilizing an open mining system, the company faces challenges related to mine drainage. Based on rainfall analysis from 2013 to 2020. the planned rainfall rate is 25.938 mm/hour, with a rainfall intensity of 5.712 mm/hour, resulting in a runoff water discharge of 0.599 m³/second. The water discharge entering the well at the site is 2159.08 m³/hour. The designed drainage channel has a discharge capacity of 3.109 m³/second, a wet surface area of 0.5 m², a channel bottom slope of 0.03%, a hydraulic radius of 0.25 m, a Manning roughness coefficient of 0.011. a wet cross-section circumference of 2 m, and a flow depth of 0.5 m. The planned well dimensions are 60 m in length, 20 m in width, and 7 m in depth, with a volume of 8400 m³. The current sludge settling pond has three compartments with a total capacity of 393.75 m³. The proposed design for the sludge settling pond includes a length of 60.6 m, a width of 15 m, a depth of 7 m, and a volume of 5454 m³. The actual mud dredging frequency is once every 2 days, while the proposed plan extends this interval to 9 days using a Doosan 340DX type excavator. This comprehensive drainage system design aims to efficiently manage runoff and sedimentation, ensuring sustainable mining operations